The Effect of Chest Physiotherapy on Airway Clearance in Toddlers with Pneumonia: A Quasi-Experimental Study - Sondang Deri Maulina Pasaribu; Tantri Wenny Sitanggang; Oryza Intan Suri (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2026)
Pneumonia remains a leading cause of morbidity among children under five, particularly in developing countries. Excessive mucus accumulation often leads to ineffective airway clearance, worsening respiratory distress. Evidence on the effectiveness of chest physiotherapy using structured clinical assessment is still limited. This study aimed to examine the effect of chest physiotherapy on airway clearance in toddlers with pneumonia. This study used a quasi-experimental design with a one group pretest–posttest design was conducted in the Melati B Inpatient Ward of RSUD Kota Cilegon in 2024. A total of 36 toddlers were recruited using purposive sampling. Airway clearance was assessed using a structured respiratory checklist, including respiratory rate, breath sounds, sputum production, and use of accessory muscles, with acceptable reliability (Cronbach’s alpha > 0.70). The intervention consisted of postural drainage, percussion, and vibration administered twice daily for three days. Data were analyzed using paired t-test (p < 0.05). Results show that the mean airway clearance score increased significantly from 3.28 ± 0.659 to 5.81 ± 0.525 after the intervention (p = 0.001). Chest physiotherapy significantly improves airway clearance in toddlers with pneumonia and can be recommended as an evidence based pediatric nursing intervention.